Tooth transposition - A literature review and a clinical case - Beatriz Silva Câmara Mattos; José Carlos Mesquita Carvalho; Márcio Matusita; Ana Paula Pereira Pinheiro Alves (Universidade Estadual de Campinas, 2015)
Tooth transposition is an anomaly in the position of teeth where two teeth of the same maxillary quadrant change their position in the dental arch. There are different types of transposition, classified according to the involved teeth. The review of the etiology of tooth transposition aims at identifying the factors related to its occurrence, and the purpose of this study is to report a case of cleft lip. Studies indicate higher prevalence of upper Canine - First Premolar transposition compared to other types of transposition, as well as a higher prevalence among females and of its unilateral occurrence. Mx.C.P1 is also related to anomalies in tooth number, especially with the agenesis of the lateral incisor. The clinical case of cleft lip and upper Canine - First premolar transposition presented in this study enables the discussion of aspects regarding the etiology of tooth transposition and of predisposing factors. Both the Mx.C.P1 transposition and cleft lip and palate are related to genetic factors and present a multifactorial inheritance pattern. The importance of prevention and early detection of tooth transposition is reaffirmed, aiming at minimizing the disturbances caused by tooth transposition. Further research on the prevalence of tooth transposition in populations with cleft lip and palate would yield a better insight about the simultaneous occurrence of these dental and oral anomalies. The therapeutic procedures for functional and cosmetic rehabilitation of the reported patient are described.